SP9.1.5 Compliance with the NELA pathway at a District General Hospital. Reducing time to theatre by limiting CT-associated delay - A prospective closed loop audit. (28th October 2021) - Ahmad, Shahrukh; Hasbullah, Nazhatul; Handa, Siddhartha; Patel, Panna
Abstract: Aim: NELA recommends rapid request, conduct and reporting of CT to reduce the delay in time to theatre and thus ultimately improving patient outcomes. Our aim was to identify and reduce delays with regards to CT scanning and reporting. Methods: Our Local Laparotomy Pathway standard recommends that CT scans be performed within one hour of being requested and reported within one hour of being performed. NELA data and electronic records were reviewed over a 3 month period (January 2020 to March 2020) - revealing that only 59% of pre-laparotomy CTs done (n = 17) complied with this standard. A dedicated "CT Emergency Laparotomy" protocol was introduced, which assigned the scan as top priority for both radiographers and radiologists. After making this change, data was prospectively collected to see if there was reduced time from CT request to report. Results: Compliance with the pathway standard for the three month period from October 2020 to January 2021 increased to 81% (n = 21). Reasons for non-compliance included patient instability, awaiting renal profile; and COVID-related deep cleaning between patients. Out of hours, CT reporting was outsourced, which led to even quicker reporting – with multiple scans being both performed and reported within one hour of the request. Of the 16 patients that fit the criteria for urgent laparotomy, 87.5% (14 patients) were operated on within 6 hours of initial intention to operate. Conclusion: Our re-audit showed that after the introduction of a dedicated laparotomy CT protocol, there was reduced time to CT report and ultimately reduced delay to Laparotomy.